Empowering Women In Politics (Study At The Regional Leadership Council Of The North Sumatra Persatuan Indonesia Party) - Wim Putra Tri Pratama S; Siti Mardiana; Maksum Syahri Lubis (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Abstract: The low participation of women in political institutions means that various women's interests are less accommodated in a number of political decisions. Research problem formulation 1) How are women empowered in politics by the North Sumatra Perindo Partai DPW? 2) What are the factors inhibiting women's empowerment in politics by the North Sumatra Perindo Partai DPW? The method used is a qualitative research method. Data collection techniques using observation, interviews and documentation. The results of research on women's empowerment in politics (the North Sumatra Perindo Partai DPW study) have gone well. The planning carried out in implementing gender responsiveness is good. This can be seen in the socialization plans made. Implementation has been maximized. With Perindo Partai’s strategy of taking a more personal approach. The evaluation achieved good results. By improving the quality of national education, the encouragement of women to take part in politics can be realized. The suggestion in the research is that the KPU Institute holds outreach that focuses on 30% representation of women. As well as making significant changes regarding the quota for DPRD members specifically for women. Can make policies that in politics gender equality is necessary. Because patriarchal culture is very irrelevant to use during elections. A long-term national campaign is needed. Which contains women's political awareness, reinterpretation of religious doctrines that take away women's political rights through the media. Both printed and electronic media such as posters, billboards, stickers and pins with images.